Changing Primary Energy Consumption Due to COVID-19: The Study 20 European Economies - Mirnezami, Seyed Reza; Rajabi, Sajad (International Journal of Energy Economics and Policy, 2020)
With the outbreak of the coronavirus in countries around the world, governments have decided to impose restrictions and social distancing. Closures of businesses, and hence changes in supply and demand patterns during this period, have deepened concerns among policy makers. In this article, we investigate the change in primary energy consumption in the 20 European countries that have the highest GDP. To this end, 10 different shock scenarios and its limitations are considered. By implementing these shocks into input-output modelling, changes in primary energy consumption are calculated. The results show that according to the best scenario (rapid and complete economy restoration), Russia with 3.5% and Italy with 2.88% will have the largest decrease, and according to the worst case scenario (explosive exacerbation of disease and complete quarantine), Spain with 14% and Italy with 13% will have the largest reduction in energy consumption. In addition, considering the total changes in primary energy consumption of these 20 countries, according to the best scenario, it will decrease by 1.81% and according to the worst-case scenario, it will decrease by 10.46%. We discuss about possibilities that energy consumption permanently declines. Keywords: Coronavirus, Input-Output Modelling, Economy of Europe, Energy Economics JEL Classifications: Q43, C67, D57, O13 DOI: https://doi.org/10.32479/ijeep.10342